2016
DOI: 10.12688/f1000research.6425.2
|View full text |Cite
|
Sign up to set email alerts
|

Is MTHFD1 polymorphism rs 2236225 (c.1958G>A) associated with the susceptibility of NSCL/P? A systematic review and meta-analysis

Abstract: Aims: To investigate the association between the methylenetetrahydrofolate dehydrogenase 1 (MTHFD1) polymorphism rs 2236225 (c.1958G>A) and susceptibility to non-syndromic cleft of the lip and/or palate (NSCL/P). Methods: An extensive literature review has been conducted using PubMed, Web of Science, Cochrane Library, Google Scholar, the China National Knowledge Infrastructure (CNKI), and Wanfang Database for eligible researches. The terms for searching were “cleft lip OR cleft palate OR CLP OR CL/P OR oral fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
2
5
0
Order By: Relevance
“…With 170 samples, the control group was considerably larger, but not consistent with HWE-. In comparison, in the other Asian (Indian and Chinese) studies that indicated a significant association of the same polymorphism and orofacial cleft, the genotypes of the control group were consistent with HWE [6,12,19]. Therefore, it appears reasonable to suggest an extension of the present study to a larger case group, for example classified according to the type of cleft, and to extend the comparison to another control group, both from the same ethnic origin.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…With 170 samples, the control group was considerably larger, but not consistent with HWE-. In comparison, in the other Asian (Indian and Chinese) studies that indicated a significant association of the same polymorphism and orofacial cleft, the genotypes of the control group were consistent with HWE [6,12,19]. Therefore, it appears reasonable to suggest an extension of the present study to a larger case group, for example classified according to the type of cleft, and to extend the comparison to another control group, both from the same ethnic origin.…”
Section: Discussionsupporting
confidence: 45%
“…The possible effects of ethnic origin, as well as the type of oral cleft (lip, palate or both), may warrant further study [4]. The conclusions have been generally consistent for a number of the reviewed studies that have included all these types of nonsyndromic cleft cases, and a wide range of populations with different ethnic origins [19,20]. Nevertheless, the overall coverage may be instructive but by no means complete: for example, the coverage on African and South-East Asian populations remains rather poor.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, previous reports suggested that TPM1 polymorphisms might also contribute to the etiology of NSCLP (Moreno Uribe et al., ; Qian et al., ). Further investigations in a large sample are needed to reach a more precise conclusion in the future (Zhao et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional factors, such as the adequacy of folic acid in the mother's diet, are clearly important, but other potential disturbances in ovulation or development of fetus may be due to the activity of key factors such as the MTHFR enzyme in folate metabolism 10,11 . In addition, the role of other polymorphisms of folate metabolism has been proven in recent meta-analyses 7,12,13 . There are six published meta-analyses related to our topic in the literature 7,8,[14][15][16][17] .…”
mentioning
confidence: 99%